Urban Expansion on Indigenous Lands. The pueblo de indios of La Toma in the Royal Audience of Buenos Aires - Tell, Sonia (Centro de Historia Argentina y Americana, 2010)
This article focuses on land conflicts in those "pueblos de indios" which were able to preserve their lands until the late nineteenth century in the jurisdiction of Cordoba. It is based on a case study: the Indian town of La Toma -which was settled near the city of Cordoba- between 1790 and 1825. More specifically, it reconstructs the attempts of the Spanish chapter, the jesuits and some landowners to occupy some pieces of land in the town, and to legalize the occupation. It also looks at the indigenous strategies for the defense of their land rights, which were supported by the Royal Audience of Buenos Aires which allowed them to avoid the restrictions imposed by local courts.